FORMATION OF STRUCTURE UNITS OF YIELDING CAPACITY AND QUALITY OF GRAIN OF NEW WINTER WHEAT VARIETIES IN NORTHERN STEPPE - Ноздріна, Н. Л. (Scientific Progress & Innovations, 2014)
The results of research concerning the definition of structure units of yielding capacity (quantity of productive stems on 1 m2, quantity of grains in an ear, mass of grain in an ear, mass of 1000 grains) and quality of grain of new varieties of winter wheat, grown on bare fallow are cited. Influence of weather conditions on yielding capacity and quality of grain is established. It is revealed that the greatest yielding capacity of all varieties has been received in 2013 year with sufficient moistening, the least - in droughty 2012 year. The varieties Zamozhnist and Antonivka were the most productive. In years different in weather conditions the best indexes of grain quality were formed by variety of Sonechko, and low – by variety Rozkishna.